THE TRUST IN THE RITUAL’S “CAMBUK BERDARAH” WHIP IN SUMBERINGIN VILLAGE BLITAR REGENCY - Novi Catur Muspita; Fandu Dyangga Pradeta (Universitas Islam Balitar, 2021)
Regional culture is the wealth of a country in strengthening national culture. The extinction of a regional culture must be watched out for, for that it is our duty together to protect and preserve regional culture. Researchers are interested in researching the tradition of the bloody whip in Sumberingin Village, Blitar Regency. The objectives of this study are: (1) to analyze the role of social capital in the preservation of the tradition of the bloody whip in Sumberingin Village, Blitar Regency, (2) to analyze the supporting and inhibiting factors in the preservation of the bloody whip tradition in Sumberingin Village, Blitar Regency. The research method is qualitative. The results showed: The conclusions are as follows: (1) The role of social capital in the Preservation of the Bloody Whip Ritual in Sumberingin Village, Blitar Regency is: (a) Bonding or social glue, which contributes separately to the occurrence of social integration, (b) Social Bridging, namely bridges. social is to form community social solidarity within the frame of willingness or volunteering or sincerity in accordance with the ability to participate actively in accordance with their respective abilities and fields, (2) Supporting factors in Preserving the Tradition of Bloody Whip to Reduce Rain in Sumberingin Village, Blitar Regency are: ( 1) the community has solidarity, togetherness in agawe or creating a celebration, (2) strong social ties between residents of the Sumberingin Village community and members of the community outside the village, fellow cultural preservationists (3) Participation and community care and cooperation between residents in realizing art performances and tradition.